خروج الطلب إلى الخبر - بابطين, ياسر بن محمد (قــــــراءات, 2019)
يتناول البحث مسألة وضع الطلب موضع الخبر، وهي إحدى صور خروج الكلام عن مقتضى الظاهر، وتقابلها مسألة وضع الخبر موضع الطلب، وبين المسألتين فروق مهمة تمنع قياس إحداهما على الأخرى، وعلى هذا انتظمت مطالب البحث الثلاثة: استعرض الأول مسألة خروج الخبر إلى الطلب. واستقرأ الثاني الفروق بين الخبر والإنشاء. وناقش الثالث شواهد خروج الطلب إلى الخبر، التي انحصرت في أربعة أنواع: الأول: مجازات الإنشاء الطلبي، والثاني: الأمر في باب التعجب، والثالث: ما ورد في سياق عطف الإنشاء على الخبر، والرابع: ما اقترن بما يمنع تصور الطلبية. وانتهى البحث إلى أنَّ شواهد "خروج الطلب إلى الخبر" ترد عليها إشكالات أقوى مما يدفعها من الاحتجاج بالقياس؛ أو الاستدلال بالقرائن؛ لأنه قياس مع الفارق، والقرائن الواردة لا تقتضي إخراج لفظ الطلب إلى معنى الخبر، بل تحتمل التجوز في كيفية الطلب أو متعلقاته دون أصله.   Abstract This paper addresses the issue of placing request styles Altalab in the position of the Reporting Alkhabar, one of the speech's characteristic when speech departs from what is assumed to be expected to the circumstance Moqtadha Aldhaher .  On the other hand, the paper discusses placing Reporting in the position of request styles. In fact, there are significant differences which obstruct the syllogism between each other. Hence, the research is divided into three sections. First, it outlines the issue of departing the reporting to the request. In the second section, it surveys the differences between the request and the reporting. In the third section, the paper analyses the departing from the reporting to the request which is limited to four types: the metaphors of informing based on the request Alensha Altalabi, command in the wonder style, what was mentioned in the context of conjunction between the informing and the reporting, and what connected with what obstructs the conception of the request . The research concludes that the examples of departing the request styles to the reporting encounters several strong objections which make these examples invalid for Syllogism because of the extreme variance. Additionally, they are not valid for inference by presumptions since they do not require departing the utterance of the request to the meaning of the reporting, but they are probably used figuratively in the way of request or its attachments Almota'aliqat not in the origin of the request meaning.